Determination of ambroxol in syrups using diffuse reflectance spectroscopy - Rufino, José L. [UNESP] (2009)
This paper reports an analytical method for the determination of ambroxol in micellar medium by spot test-diffuse reflectance spectroscopy. The reflectance measurements were performed analyzing the colored compound (λ= 520 nm) produced from the reaction between ambroxol and p-dimethylaminocinnamaldehyde on the surface filter paper. The linear range was from 1.21 × 103 to 9.65 × 103 mol L-1 (500 - 4000 μg mL-1). The limit of detection and quantification were 3.50 x 10-4 mol L-1 (145 μg mL-1) and 1.16 x 10-3 mol L-1 (481 μg mL-1), respectively. Five commercial samples were analysed and the results obtained by the proposed method were in good agreement with those obtained by the literature method at 95% confidence level.